Religiosity in Indonesia: A Descriptive Analysis Using the Centrality of Religiosity Scale - Karunia, Anindita; Syahrani, Risa Aulia (Indonesian Scientific Publication, 2024)
Indonesia has the most significant number of Muslim citizens worldwide. However, the data is based on the individual’s identity, which isn’t adequate to show their religiosity. This research aimed to describe the religiosity score among Muslims in Indonesia, and we use The Centrality of Religiosity Scale (CRS) by Huber & Huber (2012), which has been translated into Indonesian by the researcher through an adaptation process. We find that 100 respondents have high religiosity scores, 44 have average, and 90 have low religiosity scores. There are differences in sum between respondents with high and low religiosity scores. This can explain several attitudes and behaviors among our respondents, such as views on marriage, premarital sexual behavior, political views, and in-group and out-group attitudes. Religious respondents will be more likely to (1) have specific requirements when choosing their spouse, (2) have a lower attitude and are less likely to engage in premarital sexual behavior, (3) prefer Muslim candidates, and (4) have a strong in-group attitude.